MEMBANGUN MEDIA PENYIARAN YANG BERDAULAT - ROSO PRAJOKO (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Broadcast media that we meet everyday are very important in providing information, arts education, culture and various other events contained there. If we are not careful, then the broadcasting media could have a negative impact and actually violate the principles of broadcasting that is based on Pancasila and the 1945 Constitution. In this study the researchers used qualitative methods to analyze data. Qualitative research seeks to elevate ideographically various phenomena and social realities. The results of the study and discussion illustrate that most people watch and listen to the radio for more than one or two hours per day. As for what they do by watching and listening to the radio there are various kinds of goals to the needs of each audience. The positive and negative impacts depend on us who see, as well as the need for an independent monitoring agency, and are firm in overseeing the broadcast media. Do not let broadcast media actually damage national integration.